Attenuation of Chondrogenic Transformation in Vascular Smooth Muscle by Dietary Quercetin in the MGP-Deficient Mouse Model - Beazley, Kelly E. (Public Library of Science, 2013)
RATIONALE: Cartilaginous metaplasia of vascular smooth muscle (VSM) is characteristic for arterial calcification in diabetes and uremia and in the background of genetic alterations in matrix Gla protein (MGP). A better understanding of the molecular details of this process is critical for the development of novel therapeutic approaches to VSM transformation and arterial calcification. OBJECTIVE: This study aimed to identify the effects of bioflavonoid quercetin on chondrogenic transformation and calcification of VSM in the MGP-null mouse model and upon TGF-β3 stimulation in vitro, and to characterize the associated alterations in cell signaling. METHODS AND RESULTS: Molecular analysis revealed activation of β-catenin signaling in cartilaginous metaplasia in Mgp-/- aortae in vivo and during chondrogenic transformation of VSMCs in vitro. Quercetin intercepted chondrogenic transformation of VSM and blocked activation of β-catenin both in vivo and in vitro. Although dietary quercetin drastically attenuated calcifying cartilaginous metaplasia in Mgp-/- animals, approximately one-half of total vascular calcium mineral remained as depositions along elastic lamellae. CONCLUSION: Quercetin is potent in preventing VSM chondrogenic transformation caused by diverse stimuli. Combined with the demonstrated efficiency of dietary quercetin in preventing ectopic chondrogenesis in the MGP-null vasculature, these findings indicate a potentially broad therapeutic applicability of this safe for human consumption bioflavonoid in the therapy of cardiovascular conditions linked to cartilaginous metaplasia of VSM. Elastocalcinosis is a major component of MGP-null vascular disease and is controlled by a mechanism different from chondrogenic transformation of VSM and not sensitive to quercetin.